Edukasi Latihan Brain Gym terhadap Peningkatan Kemampuan Fokus Membaca Anak - Anak Usia 5 Tahun - Riani Baiduri Siregar; Rudi Purwana; Heri Saputra; Ani Ramdhani Kaban (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Healthy children are in perfect condition both physically, mentally/psychologically and socially (free from disease, weakness and disability). In order for children to grow and develop optimally, children must also be accustomed to healthy living behavior and the Childhood Phase is the developmental phase from the age of 1 or 2 years to 10-12 years, this phase is further classified into two, namely early childhood (small children) between 1-6 years, and later childhood (big children) between 6-12 years. According to the Ministry of Education and Culture, reading mastery is not mandatory for PAUD age children (3-5 years) because this skill will only be taught formally at elementary school level. Children should actually start being taught to read maximally at the age of 4-6 years. Because, this is a golden period for the cognitive development of the brain. In other words, they can absorb lessons and imitate quickly. Brain gym or brain exercise is a touch that can stimulate the work and functioning of the brain optimally, namely further activating the abilities of the right and left brain, so that cooperation between the right and left brain hemispheres can be established. This can improve memory in the child's brain to learn to read.